Materia médica : Rareza, singularidad y accidente en la España temprano-moderna - Río Parra, Elena del (Book collections on Project MUSE., 2017)
"Materia medica explores the intersection of the sciences and humanities in Spanish sixteenth and seventeenth century representations of the extraordinary within the larger scheme of the Baroque. Medical and chirurgical treatises, discourses, letters, broadsheets, and paratexts of the period share with the humanities thought processes, methods, patterns, and--most importantly--some forms of description. Archival evidence broadens the spectrum of these texts, and cases are frequently compared to similar instances in disciplines such as theology, literature, and the law. Materia medica maps, among other notions, the imagination, the spectacular, the legendary and the "novelesque" in scientific writing, and examines the influence of the theatrical in representations of medical cases as stated by doctors themselves. The analyses of Materia medica tilt between the world of fact and fantasy, and explore the effect of the descriptions of its cases on the social sphere. An eclectic monograph, it is intended for specialists in both early-modern culture and intellectual history. It also appeals to scholars who are particularly interested in the history of the rare, the unusual, and the monstrous, a fertile niche that is very much in the spirit of sixteenth and seventeenth century Western thought."--Provided by publisher.